A look at the high energy aspects of the supernova remnant G309.8+00.0 with eROSITA and Fermi -LAT - Michailidis, M.; Pühlhofer, G.; Santangelo, A.; Sasaki, Manami; Becker, W. (Astronomy & Astrophysics, 2024)
Supernova remnant (SNR) detection along the Galactic plane poses a number of challenges. A diffuse X-ray emission component emanating from unidentified sources on the Galactic plane further complicates such a detection in X-rays. Due to the presence of dense dust clouds along the Galactic plane, X-ray photons are also subject to high absorption. Similarly, diffuse signals from the Galactic plane cause γ-ray contamination from the signal of individual objects. The SNR G309.8+00.0 lies exactly on the Galactic plane, with its center coinciding with galactic latitude (b) = 0. In this paper we report the first detection of the SNR G309.8+00.0 in X-rays and γ rays, using stacked data from the first four consecutive extended ROentgen Survey Imaging Telescope Array (eROSITA) - on board the Russian-German Spektrum Roentgen Gamma (SRG) - all-sky surveys (eRASS:4) and 15.5 yr of Pass 8 data recorded from Fermi-LAT, respectively. The SNR appears to have an elliptical shape of 0. ° 43 × 0. ° 32 in size in both radio synchrotron and X-ray data. The SNR's emission exhibits a shell-like morphology and good spatial correlation in both energy bands. The X-ray emission was solely detected in the 1- 2 keV energy band (subject to strong absorption at soft X-rays) and the spectral analysis results of eRASS:4 data present a purely thermal SNR with a high absorption column density 3.1+0.7-0.5 1022 cm-2 3. 1 - 0.5 + 0.7 · 10 22 cm - 2 and a temperature of 0.34±0.1 keV. Although the thermal plasma appears to be in equilibrium, the limited statistics do not allow us to exclude nonequilibrium models. The X-ray spectral analysis of the remnant resulted in the detection of relatively (given the limited statistics) prominent Mg triplet lines at 1.33- 1.47 keV and silicon (Si XIII) at 1.74- 1.9 keV energies. In combination with optical extinction data, the absorption column density values derived from the remnant's spectral analysis support a remnant's distance greater than 6 kpc, rather than a 3.12 kpc distance as reported in the literature, and yield an age of 1-3.5 105 yr. Employing 15.5 yr of Fermi-LAT γ-ray data at and around the remnant's vicinity, we confirm the detection of the to-date unidentified 4FGL J1349.5-6206c source that can either be modeled as a single source or a conglomerate of multiple distinct source components. In the latter case, the detailed inspection of the Fermi-LAT γ-ray data in the direction of the remnant allowed us to decompose the 4FGL J1349.5-6206c source into four point-like components, among which one is spatially coincident with the SNR G309.8+00.0 shell. We detected the component that spatially coincides with the SNR with a significance of 5.8σ above 1 GeV with Fermi-LAT and thus argue that the SNR G309.8+00.0 likely represents at least a significant portion (if not all) of the emission from the 4FGL J1349.5-6206c γ-ray source, detected with 9.8σ significance > 1 GeV with Fermi-LAT.
CRIS-Team Scopus Importer:2024-10-04
Keywords: Acceleration of particles; Cosmic rays; Gamma rays: ISM; ISM: supernova remnants; X-rays: individuals: G309.8+00.0; X-rays: ISM